PENGARUH PERENCANAAN PAJAK, STRUKTUR MODAL DAN KEPEMILIKAN MANAJERIAL TERHADAP NILAI PERUSAHAAN DENGAN TRANSPARANSI PERUSAHAAN SEBAGAI VARIABEL MODERASI - Deaelma Sari; Wiwit Irawati (JURNAL AKUNTANSI BARELANG, 2022)
This study aims to identify and prove empirically the effect of Tax Planning, Capital Structure and Managerial Ownership on Firm Value with Corporate Transparency as a moderating variable. This type of research is quantitative approach research with explanatory research and associative methods. Samples were taken using the purposive sampling technique using Eviews 9 software for data analysis. The sample consists of 60 data from 12 property and real estate subsector manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The results show that Tax Planning, Capital Structure and Managerial Ownership simultaneously affect the value of the company which is moderated by corporate transparency, tax planning has no effect on firm value, the capital structure does not affect firm value, managerial ownership does not affect firm value, and corporate transparency does not. effect on firm value, corporate transparency is unable to moderate the relationship between tax planning and firm value, corporate transparency is unable to moderate the relationship between capital structure and firm value, and corporate transparency is unable to moderate the relationship between managerial ownership and firm value.